2020
DOI: 10.3390/jpm10040205
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of miRNA Expression in Patients with Rheumatoid Arthritis during Olokizumab Treatment

Abstract: Rheumatoid arthritis (RA) is the most common autoimmune disease worldwide. Epigenetic alternations of microRNAs (miRNAs) can contribute to its pathogenesis and progression. As the first line therapy with DMARDs is not always successful, other drugs and therapeutic targets should be applied. This study aims to measure the expression level of plasma miRNAs in RA patients treated with olokizumab and to evaluate their potential as prognostic biomarkers. The expression of 9 miRNAs was quantified in 103 RA patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…268 Furthermore, baseline plasma levels of miR-26b, miR-29, miR-451, and miR-522 in RA patients appear to be predictors of response to OKZ therapy, although the findings were derived from a Russian population. 269 MiRNA-BASED THERAPEUTIC STRATEGIES FOR RA Modern therapies for RA aim to achieve remission or at least low disease activity within 6 months, which is fulfilled by a treat-to-target strategy that involves rigorous disease control and individualized management. 270 To date, the first-line medication for RA patients has been cDMARDs, primarily MTX, supplemented with glucocorticoids and/or nonsteroidal anti-inflammatory drugs.…”
Section: Contribution To Prevention and Precise Diagnosismentioning
confidence: 99%
“…268 Furthermore, baseline plasma levels of miR-26b, miR-29, miR-451, and miR-522 in RA patients appear to be predictors of response to OKZ therapy, although the findings were derived from a Russian population. 269 MiRNA-BASED THERAPEUTIC STRATEGIES FOR RA Modern therapies for RA aim to achieve remission or at least low disease activity within 6 months, which is fulfilled by a treat-to-target strategy that involves rigorous disease control and individualized management. 270 To date, the first-line medication for RA patients has been cDMARDs, primarily MTX, supplemented with glucocorticoids and/or nonsteroidal anti-inflammatory drugs.…”
Section: Contribution To Prevention and Precise Diagnosismentioning
confidence: 99%
“…MTX has been shown to cause increased marrow adiposity and reduced trabecular bone volume; it has been reported that MTX upregulates miR-6315 after treatment, which might be a vital cause of bone and marrow fat formation [138]. Similarly, statistically significant differences between miR-26b, miR-29, miR-451, and miR-522 were observed after olokizumab therapy [139].…”
Section: Micro Rnamentioning
confidence: 99%
“…lnc-ITSN1-2 could be a convincing biomarker for RA diagnosis and monitoring of disease activity as it is significantly upregulated in the plasma and synovial tissues of RA patients and positively correlated with DAS28, ESR, and CRP. Notably, the ROC curve analysis showed that lnc-ITSN1-2 had good diagnostic value (AUC = 0.898, specificity = 80%, and sensitivity = 90%) ( 145 , 146 ).…”
Section: Candidate Rnas As Biomarkers For Ramentioning
confidence: 99%